A Pengembangan Instrumen Penilaian Tiga Ranah Berbasis HOTS Pada Mata Pelajaran PAI-BP di SMP - Rizky Rahayu; Fuji Pratami; Ali Jusrin Pohan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The purpose of this study was to find out the description of the PAI-BP learning assessment process before and after, the validity and practicality of developing HOTS-based three-domain assessment instruments in class VIII SMPN 2 Panyabungan on the material